FAKTOR PENENTU CASH HOLDING PERUSAHAAN CONSUMER NON-CYCLICALS - Putri, Indah Permatasari Zafari; Suhendah, Rousilita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to analyze whether there is an effect of leverage, net working capital, firm size, growth opportunity, and profitability on cash holding. This research uses quantitative methods with a total data sample of 38 consumer non-cyclical companies for the 2020-2022 period. The data sampling technique uses purposive sampling with predetermined criteria. The data was processed and tested using Microsoft Excel 2021 and the E-Views 12 Student Version Lite application. The results of this study indicate that profitability has a significant positive effect on cash holding, while leverage, net working capital, firm size, and growth opportunity have no effect on cash holding. The implication of this research is expected to provide an overview of the effectiveness of cash holding in a company so that investment opportunities are open to investors.